The use of hyper-hidden markov models in wireless channel simulation - Boadi, Antonia Marie (2005 Winter Simulation, 2005)
The transmission of multimedia over satellite, cellular or mobile wireless networks introduces impairments which degrade signal quality. This thesis proposes a channel simulation model and design philosophy that represents a shift from the use of traditional network-centric design requirements to a more comprehensive approach that encompasses perceptual quality issues. PerFEC, the Perceptually-Sensitive Forward Error Control agent, employs a flexible, adaptive coding scheme that is both quality-of-service (QoS) and quality-of-perception (QoP) configurable. PerFEC is a decision agent that uses decoder output to select an error control scheme that is appropriate for the prevailing channel conditions. The channel simulation model is based on a new construct, the Hyper-Hidden Markov Model (HHMM), whose internal states have dual interpretation: they represent the user's perceptual quality as well as an estimate of the current bit-errorrate. This layering of Hidden Markov Models provides insight into the nonlinear relationship between quality-of-service metrics and perceptual quality.